FLoccuLAnoN CHARACTErusncs OF P0LYACRYLAMIDE-S0o1uM CARBOXYL METHYL CELLULOSE GRAFT COPOLYMER (Biological Sciences - PJSIR, 2002)
Preparation of polyacrylamide- sodium carboxyl methylcellulose graft having a percentage  graft on  level of 527.21% and  graft polyacrylamide chains of 1.22 x 105 viscosity average molecular weight is described. A comparative water treatment  study with particular emphasis on the flocculation potentials of the graft copolymer  with  alu minium  sulphate,  ferric sulphate and polyacrylamide using Warri River water sample is reported. The  graft  copolymer  was  not  only  found  to exhibit relatively good flocculation characteristics but was significantly found not to impact treated water with any polymer residue. When used with aluminium  sulphate in the ratio of 4:1, the turbidity  of test water improved  from 43.4 NIU  to as  low  as  0.008 NIU.